Constructing a correlation between ferroelectricity and grain sizes in Hf0.5Zr0.5O2 ferroelectric thin films. Issue 9 (10th February 2022) - Chen, Haiyan; Luo, Hang; Yuan, Xi; Zhang, Dou
Abstract : A correlation between ferroelectricity and grain sizes was constructed through controlling process conditions including annealing conditions and film thickness. Abstract : A correlation between ferroelectricity and grain sizes in atomic layer deposition (ALD)-derived Hf0.5 Zr0.5 O2 (HZO) thin films has been demonstrated through controlling process conditions. The influence of annealing temperature, annealing time and film thickness on the structural properties, ferroelectric performance and grain sizes was systematically investigated. A correlation diagram was constructed according to the different values of remnant polarization ( P r ) and coercive field ( E c ) in the different ranges of grain sizes. The P r values displayed a continuous declining trend, and the E c values firstly decreased and then increased with the increase of grain sizes. A strong size effect of ferroelectricity in the HZO thin films was proved through providing a simple annealing process or controlling the film thickness. The results showed that excellent ferroelectricity (∼15 μC cm −2 ) could be obtained with grain sizes in the range of 15–35 nm, which corresponded to the appropriate annealing conditions of 450 °C for 60 s with a film thickness of 10 nm. This paper can provide guidance for designing ferroelectric HfO2 -based films with high performance through controlling grain sizes.